Description Of Characteristics, Diagnosis And Financing Of BPJS Patients In ENT Poly Health Service Facility Level 2 - Roesbiantoro, Andi; Budhi Setianto; Adriansyah, Agus Aan; Pulih Asih, Akas Yekti; Setiyowati, Eppy; Bistara, Difran Nobel; Sa'adah, Nikmatus (Universitas Nahdlatul Ulama Surabaya, 2022)
The application of tariff applied in handling BPJS patients references the INA- CBGs and the payment model used by BPJS Kesehatan to replace the total bill by the hospital. Hospitals receive payments based on the INA- CBGs rate, which is the average cost spent by a group of diagnoses. It is expected to improve the quality and efficiency of hospitals. The benefit of implementing INA -CBGs in JKN is the tariffs in the form of packages cover all components of hospital costs. Cost efficiency efforts must be made. That is no deficit from the applicable INA-CBGS tariff. Quality and cost control efforts are very important in the implementation of ENT specialist poly services. This study aims to analyze the demographic characteristics of the patient, the patient's diagnosis, the difference in rates between INA CBGS payments and RSIS rates, the composition of financing and the Unit Cost of ENT Polyclinics. The research type is quantitative observational with cross-sectional design. The research location is at the Surabaya Islamic Hospital with BPJS TXT data, processing in January-December 2019. The results showed, the demographic characteristics of most patients were > 50 years old, and most of them were diagnosed with minor chronic diseases. The difference between Ina-CBGS payments and RSIS rates is Rp. 60,174 which means that each patient contributes a profit of Rp. 60,174. The composition of the financing for implementation of the ENT Polyclinic is the cost of consulting services. The unit cost of ENT Polyclinic patients is Rp. 132,774 per patient.